DENSITY AND DISTRIBUTION OF BAMBOO IN THE WILDLIFE CONSERVATION AREA OF WAT KLAI KANG WON (KHAO SARAPUDDEE SRI CHAROENTHUM), HUNKA DISTRICT, CHAI NAT PROVINCE - Sornprasert, Ratapol; Hambananda, Anong; Dommran, Narinthorn; Tarnsap, arudsri; Cheteng, Nasimah; Aroonsrimorakot, Sayam; Jonganurak, Thanongsak; Siripatho, Phra Athikan Samruam; Khantithammo, Phra Manoon (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The density of bamboo in the wildlife conservation area of Wat Klai Kang Won, the sample of 34 plots equal to 68 Hectares (425 Rais) found 5 species of bamboo of 1,035 clumps, the most were Phai Rual (Thyrsostachys siamensis), the second were Phai Pa (Bambusa bambos), Phai Leung (B. multiplex), Phai Si Suk (B. blumeana), Phai Num Tao (B. ventricosa) and the clumps were 865, 82, 60, 24 and 4 clumps respectively. The density was 15-22 clumps/Hectare. Phai Num Tao has the lowest density of 0.06 clumps/Hectare. Phai Rual has the highest density of 12.72 clumps/Hectare. The least dense plot No. 31 equal to 2.00 clumps/Hectare. The most density was plot No.11 equal to 46.00 clumps/Hectare. The total bamboo clum of 5 species were 46,624 clum which is the highest Phai Rual. Followed by Phai Si Suk, Phai Pa, Phai Leung and Phai Num Tao were 26,340, 13,710, 4,974, 1,541 and 59 clum respectively. The density was 685.64 clum/Hectare, whereas the lowest density was Phai Num Tao was 0.86 clum/Hectare. The highest density was Phai Rual 387.35 clum/Hectare. The distribution of 5 species were 1,035 clumps in 34 plots which divided into 4 parts found that part 2 had highest distribution follow by part 3, 4, 1 were 307, 300, 227 and 201 clumps respectively. The part 2 had Phai Rual, Phai Pa, Phai Leung, Phai Si Suk and Phai Num Tao has density of 243, 46, 10, 4 and 4 clumps respectively.